2014
DOI: 10.3920/qas2013.0314
|View full text |Cite
|
Sign up to set email alerts
|

Tropane alkaloids in food: poisoning incidents

Abstract: Other TAs are known stimulants, such as cocaine and cocaine-related alkaloids. These will not be discussed in this review as these compounds are drugs of abuse and not related to food.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 40 publications
(53 reference statements)
1
75
0
4
Order By: Relevance
“…In another hand, Liou et al confirmed anti-inflammatory activity of two components (lawsochylin 1 and lawsonaphthoate A) from L. inermis these molecules inhibit superoxide anion generation in inflammation process [45]. Plants that were identified as having hallucinogenic effects belong to three species, namely, H. muticus L., D. stramonium L., and M. fragrans L. These results are in accordance with the well-established result of toxicological studies showing hallucination symptoms appearing following ingestion of high doses of H. muticus and D. stramonium L. [46,47].…”
Section: Discussionsupporting
confidence: 80%
“…In another hand, Liou et al confirmed anti-inflammatory activity of two components (lawsochylin 1 and lawsonaphthoate A) from L. inermis these molecules inhibit superoxide anion generation in inflammation process [45]. Plants that were identified as having hallucinogenic effects belong to three species, namely, H. muticus L., D. stramonium L., and M. fragrans L. These results are in accordance with the well-established result of toxicological studies showing hallucination symptoms appearing following ingestion of high doses of H. muticus and D. stramonium L. [46,47].…”
Section: Discussionsupporting
confidence: 80%
“…Terms & Conditions of access and use can be found at http:// www.tandfonline.com/page/terms-and-conditions Introduction Tropane alkaloids (TAs) are toxic secondary metabolites produced by plants of several families, most notably from Solanaceae that comprise inter alia the genera Datura (thorn apple), Atropa (deadly nightshade), Hyoscyamus (henbane), Mandragora (mandrake), and Scopolia. TAs are found in all parts of the plants and are responsible for the toxic effects (EFSA 2013;Adamse et al 2014). The group of TAs today encompasses more than 200 compounds and the wide range arises from the esterification of the base compound tropanol with a variety of acids, most importantly with tropic acid.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…A report from Adamse and van Egmond (2010) clearly points to contamination with seeds from D. stramonium (Jimson weed or thorn apple) as the most common problem. However, also seeds from other Datura spp.…”
Section: Species Of Relevance For Food and Feedmentioning
confidence: 99%
“…However, also seeds from other Datura spp. as well as berries of Atropa belladonna (deadly nightshade) (Adamse and van Egmond, 2010) and seeds of Hyoscyamus niger (henbane) have been reported as impurities in food (see Section 4.1). For feed materials, five sources of TA contamination were identified by van Kempen (1992), namely D. stramonium, D. ferox, D. metel, D. wrightii and D. inoxia, of which only the first two mentioned species were estimated to occur in relevant quantities in feed materials imported to Europe (Bucher and Meszaros, 1989 (Berkov and Zayed, 2004;Berkov et al, 2006;Doncheva et al, 2006;Philipov et al, 2007).…”
Section: Species Of Relevance For Food and Feedmentioning
confidence: 99%
See 1 more Smart Citation